2019
DOI: 10.11114/jets.v7i7.4244
|View full text |Cite
|
Sign up to set email alerts
|

Moral Disengagement and Aggression in Fight Sport Athletes

Abstract: The goal of this study is to investigate the moral disengagement and aggression levels of fight sport athletes according to several independent variables and reveal the relationship among them. The study group consisted of totally 207 fight sport athletes, 88 females and 119 males with age  = 21,99 ± 4,92 and year of sport  = 6,14 ± 5,42. “The Scale of Moral Disengagement in Sport” and “The Questionnaire of Buss-Perry Aggression” were used as data collection tools. Descriptive statistics, t test, ANOVA and Pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Deceptive actions associated with athletes’ manipulation of the rules of the sports contest were justified to a larger extent by athletes with more experience in sports and by younger athletes. Regarding aggression, youth playing contact sports tended to report higher levels of moral disengagement than athletes in non-contact sports and a higher perception of legitimacy of aggressive behaviour in competition [ 74 ]. The study also confirmed the existence of age differences in moral disengagement, where younger athletes (17–18 years) tended to report higher levels than older athletes.…”
Section: Moral Disengagement As a Predictor Of Antisocial Behaviourmentioning
confidence: 99%
“…Deceptive actions associated with athletes’ manipulation of the rules of the sports contest were justified to a larger extent by athletes with more experience in sports and by younger athletes. Regarding aggression, youth playing contact sports tended to report higher levels of moral disengagement than athletes in non-contact sports and a higher perception of legitimacy of aggressive behaviour in competition [ 74 ]. The study also confirmed the existence of age differences in moral disengagement, where younger athletes (17–18 years) tended to report higher levels than older athletes.…”
Section: Moral Disengagement As a Predictor Of Antisocial Behaviourmentioning
confidence: 99%